2020
DOI: 10.1186/s13018-020-01662-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluations of diaphysis malignant tumors of femur and tibia treated with microwave ablation in situ

Abstract: Background This study was designed to evaluate the clinical outcomes of patients with diaphysis malignant tumors of femur and tibia treated with microwave ablation (MWA) in situ. Methods Retrospective study of 32 patients with diaphysis malignant bone tumors of femur or tibia have been treated by microwave ablation. Instead of en bloc resection, hyperthermia ablation in situ was carried out followed by strengthen procedure. The patients were followed up for a period ranging from 36 to 180 months. Results Twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…There has been a lack of comprehensive evaluation of the MIST/MWA technology for giant cell tumor of bone in the academic community. While many studies have focused on primary malignant bone tumors and shown promising results [11], the controversy over limb-salvage treatment persists. Additionally, the use of targeted drugs like denosumab has overshadowed the existing de ciencies in clinical treatment of GCTB.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been a lack of comprehensive evaluation of the MIST/MWA technology for giant cell tumor of bone in the academic community. While many studies have focused on primary malignant bone tumors and shown promising results [11], the controversy over limb-salvage treatment persists. Additionally, the use of targeted drugs like denosumab has overshadowed the existing de ciencies in clinical treatment of GCTB.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…On the other hand, research on primary and metastatic malignant tumors of the bone continues to yield high-quality literature reporting satisfactory clinical outcomes. However, the question of whether MIST can be used as an e cient and safe alternative to wide resection or amputation, not only as an adjunctive therapy, remains a topic of ongoing debate [11]. In the context of invasive tumors, there is a lack of in-depth discussions on the e cacy of MIST for giant cell tumors of bone (GCTB), research ndings are mixed and submerged into some massive comprehensive studies.…”
Section: Introductionmentioning
confidence: 99%